1977
DOI: 10.1029/ja082i001p00173
|View full text |Cite
|
Sign up to set email alerts
|

A search for a general gradient in the solar wind speed at low solar latitudes

Abstract: Long-term averages of solar wind speed data obtained in the ecliptic plane from July 1964 through December 1975 have been examined for a regular variation in flow speed associated with the earth's yearly excursion to latitudes +7•t ø about the solar equator. Regular speed modulations of •70 km s -x peaking at the highest latitudes are discernible from mid-1964 through 1966 and from early 1969 to early 1971. During the remainder of this lit-year interval the modulations in speed seem to be aperiodic. A superpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For Cartington rotations 1625-1626 they found large gradients (>_30 km s -• deg -•, and even perhaps >-100 km s -• deg-•), associated with the stream structure and with the boundaries of coronal holes identified in K coronal contours. They concluded that average gradients reported in several long-term studies [Hundhausen et al, 1971;Smith, 1975, 1976a, b;Bame et al, 1977;Dennison and Hewish, 1967;Coles and Rickett, 1976] are consistent with the view that high-speed solar wind emerges from coronal holes and that the increasing incidence of coronal holes between the equator and the polar caps as observed during Skylab would explain the increase in the average solar wind with latitude. Summarizing the consensus of the Skylab Workshop on Coronal Holes, Hundhausen [1977] and Levine [1977] suggested that at least during the Skylab period the solar polar cap coronal holes are steady sources of high-speed flow and furthermore that the observed gradients are consistent with a longitudinal average over a structure containing much steeper local latitudinal gradients.…”
Section: Introductionmentioning
confidence: 57%
“…For Cartington rotations 1625-1626 they found large gradients (>_30 km s -• deg -•, and even perhaps >-100 km s -• deg-•), associated with the stream structure and with the boundaries of coronal holes identified in K coronal contours. They concluded that average gradients reported in several long-term studies [Hundhausen et al, 1971;Smith, 1975, 1976a, b;Bame et al, 1977;Dennison and Hewish, 1967;Coles and Rickett, 1976] are consistent with the view that high-speed solar wind emerges from coronal holes and that the increasing incidence of coronal holes between the equator and the polar caps as observed during Skylab would explain the increase in the average solar wind with latitude. Summarizing the consensus of the Skylab Workshop on Coronal Holes, Hundhausen [1977] and Levine [1977] suggested that at least during the Skylab period the solar polar cap coronal holes are steady sources of high-speed flow and furthermore that the observed gradients are consistent with a longitudinal average over a structure containing much steeper local latitudinal gradients.…”
Section: Introductionmentioning
confidence: 57%
“…However, this type of variation is probably of more than academic interest. Solar wind observations from 1974 to 1975 show a simple recurrent pattern of two high-speed streams imbedded in magnetic sectors of opposite polarity [Bame et al, 1977;Gosling et al, 1976;Svalgaard, 1977]. Hundhausen [1977] has suggested that this pattern reflects a spatial variation in solar wind speed similar to that assumed above, with a = 30 ø and # • 25ø; the belt of slow solar wind is centered on a magnetic neutral line encircling the sun but tilted at •30 ø to the solar equator.…”
Section: These Resultsmentioning
confidence: 99%
“…For example, during the interval including January 1968 through May 1971 a gradient could not be found in data from earth-orbiting spacecraft [Diodato et al, 1974;Diodato and Moreno, 1976]. A study of the time interval 1964-1975 [Bame et al, 1977] showed the presence of an average gradient of solar wind speed with hellographic latitude during two parts of the overall period, but when the entire 12-year period was averaged, a general gradient was not apparent above background speed variations.…”
Section: Introductionmentioning
confidence: 97%